Purification and characterization of Alu I methylase - Han, Moon H. (2012)
Alu I methylase has been isolated from 300g (wet weight) cells of Arthrobacter luteus. After ammonium sulfate fractionation, the protein which has methylase activity was purified through phosphocellulose, DEAE-cellulose, Heparin agarose, and Hydroxylapatite column chromatography. The methylated DNA by the purified methylase was resistatnt against Alu I endonuclease. The purified Alu I methylase was essentially homogeneous as judged by 10% SDS-polyacrylamide gel electrophoresis, and the apparent subunit molecular weight was 56,000±1,000. The specific activity of the enzyme was 1.32 × 105 units per mg protein.